Puberty in a case with novel 17-hydroxylase mutation and the putative role of estrogen in development of pubic hair - (:unkn) unknown (BIOSCIENTIFICA LTD, 2009)
Objective: 17-Hydroxylase/17,20-lyase deficiency (17OHD) results from mutations in the CYP17A1 gene. leading to failure to synthesize cortisol, adrenal androgens, and gonadal steroids. Adrenarche is a consequence of the increased production of adrenal androgens. Here, we report a case carrying novel R239Q mutation causing complete functional loss of CYP17A1, and thus absence of adrenal and gonadal sex hormone production. The patient has had unexpected pubic hair development and insufficient breast development with estrogen replacement therapy. Possible mechanisms leading to pubic hair development and breast underdevelopment are discussed. Patient and methods: A 15-year-old female born to consanguineous parents presented with the lack of full breast development and irregular menses after the age of 14 years. She had Tanner III breast development on one side. Tanner I on the other side and Tanner I pubic hair and, no axillary hair development. The serum levels of FSH. LH, and progesterone were high and, estradiol was low The measurement of basal and ACTH-stimulated steroids was consistent with the diagnosis of 17OHD. Genetic analysis revealed novel homozygous mutation R239Q in CYP17A1 gene. Therapy with hydrocortisone was initiated and followed by the addition of conjugated estrogen. Her breast development did not improve considerably, however, pubic hair development started after estrogen treatment in spite of undetectable serum levels of androgens. Conclusion: This case study suggests that estrogen exerts a permissive effect on pubic hair development in girls, even in the presence or very low-circulating androgens, and impaired breast development might be due to estrogen/progesterone imbalance in breast tissue.
Keywords: COMBINED 17-ALPHA-HYDROXYLASE/17,20-LYASE DEFICIENCY; ANDROGEN INSENSITIVITY SYNDROME; COMPOUND HETEROZYGOUS MUTATIONS; ABSENT ENZYME-ACTIVITY; CYP17 GENE; DEHYDROEPIANDROSTERONE-SULFATE; 17,20-LYASE DEFICIENCY; ADDISONS-DISEASE; ADRENARCHE; P450C17